Sonoelastographic Findings of Carpal Tunnel Injection - Klauser, A. S.; Miyamoto, H.; Martinoli, C.; Tagliafico, A. S.; Szantkay, J.; Feuchtner, G.; Jaschke, W. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Purpose: The objectives of this study were to compare sonoelastographic color findings of the perineural area between carpal tunnel syndrome patients and healthy volunteers, and to analyze elastographic findings in that area before and immediately after intracarpal tunnel injection in carpal tunnel syndrome patients.Materials and Methods: We studied both hands of 15 healthy volunteers (7 men, 8 women; mean age: 60.1 years, range: 41 – 88 years) and 72 hands from 70 patients with symptomatic carpal tunnel syndrome (24 men, 46 women; mean age: 54.2 years, range: 24 – 83 years). Sonoelastographic color distribution was assessed in the perineural area between the median nerve and adjacent flexor tendons. The color elastograms were graded using the following system: Grade 1 as red (softest), grade 2 as yellow (soft), grade 3 as green (hard), grade 4 as blue (hardest). The patients were treated with corticosteroid injection and were reassessed with sonoelastography immediately after the injection.Results: The median color grading in the perineural area of carpal tunnel syndrome patients was grade 3 (3.1 ± 0.3, mean ± 95 % Cl), which was stiffer than that of healthy volunteers (grade 1, 1.9 ± 0.4) (p < 0.0001). Immediately after injection, the diffusion of the injected fluid was observed as having a softer appearance (grade 1, 1.4 ± 0.2) (p < 0.0001).Conclusion: The perineural area surrounding the median nerve in carpal tunnel syndrome patients was stiffer than that in healthy volunteers. Diffusion of the injected fluid in the carpal tunnel was seen as a softer finding after injection in real time using sonoelastography.
Keywords: sonoelastography; carpal tunnel syndrome; steroid injection; ultrasound; nervous-peripheral; hand